Microcomputers (components & applications) [ - Numbers, Shila (New York : Learning Press, 2014)
This handbook explains about components & applications of microcomputers
1. Introduction to microcomputer -- 2. CP/M -- 3. CHIP-8 -- 4. Dbase -- 5. Minicomputer -- 6. ZX Spectrum -- 7. Single-board computer -- 8. AIM-65 -- 9. Heathkit H8 -- 10. Laptop -- 11. Microprocessor
Keywords: Microcomputers